A Dual‐Salt Gel Polymer Electrolyte with 3D Cross‐Linked Polymer Network for Dendrite‐Free Lithium Metal Batteries. Issue 9 (13th July 2018) - Fan, Wei; Li, Nian‐Wu; Zhang, Xiuling; Zhao, Shuyu; Cao, Ran; Yin, Yingying; Xing, Yi; Wang, Jiaona; Guo, Yu‐Guo; Li, Congju
Abstract: Lithium metal batteries show great potential in energy storage because of their high energy density. Nevertheless, building a stable solid electrolyte interphase (SEI) and restraining the dendrite growth are difficult to realize with traditional liquid electrolytes. Solid and gel electrolytes are considered promising candidates to restrain the dendrites growth, while they are still limited by low ionic conductivity and incompatible interphases. Herein, a dual‐salt (LiTFSI‐LiPF6 ) gel polymer electrolyte (GPE) with 3D cross‐linked polymer network is designed to address these issues. By introducing a dual salt in 3D structure fabricated using an in situ polymerization method, the 3D‐GPE exhibits a high ionic conductivity (0.56 mS cm −1 at room temperature) and builds a robust and conductive SEI on the lithium metal surface. Consequently, the Li metal batteries using 3D‐GPE can markedly reduce the dendrite growth and achieve 87.93% capacity retention after cycling for 300 cycles. This work demonstrates a promising method to design electrolytes for lithium metal batteries. Abstract : A 3D cross‐linked gel polymer electrolyte shows effective function in uniform lithium deposition compared with traditional liquid electrolytes. The formation of stable interphase effectively restrains lithium dendrite growth, and contributes greatly to lithium cycling performance, achieving 87.93% capacity retention after cycling for 300 cycles at room temperature.